1963
DOI: 10.1111/j.1748-1716.1963.tb02572.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Studies in Well Trained Athletes at Rest and During Heavy Exercise, with Special Reference to Stroke Volume and the Influence of Body Position

Abstract: Eight well trained athletes (cyclists) with large dimensions of the circulatory system were studied with heart catheterization at rest and during exercise at 800 and 1,600 kpm/min both while sitting and supine. The results are compared with data from non‐athletes. The cardiac output at rest and during work showed the same relation to the oxygen uptake as in nonathletes. The cardiac output was less in the sitting than in the supine position by 2.6 1/min at rest and 1.8 1/min during heavy work, due to a smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
80
2
2

Year Published

1968
1968
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(96 citation statements)
references
References 48 publications
12
80
2
2
Order By: Relevance
“…Hemodynamic studies have generally, but not unanimously, shown that stroke volume increases with transition from rest to exercise in both the upright and supine positions. ", 4,[8][9][10][40][41][42] LV end-diastolic volume during supine exercise has been shown to decrease in studies in which metallic epicardial markers" and angiography were used.14 Using angiography, Gorlin et al12 found no substantial change in LV enddiastolic volume. Crawford et al6 demonstrated echocardiographically that diastolic diameter does not change during moderate supine and upright bicycle exercise.…”
Section: The Effects Of Exercisementioning
confidence: 99%
“…Hemodynamic studies have generally, but not unanimously, shown that stroke volume increases with transition from rest to exercise in both the upright and supine positions. ", 4,[8][9][10][40][41][42] LV end-diastolic volume during supine exercise has been shown to decrease in studies in which metallic epicardial markers" and angiography were used.14 Using angiography, Gorlin et al12 found no substantial change in LV enddiastolic volume. Crawford et al6 demonstrated echocardiographically that diastolic diameter does not change during moderate supine and upright bicycle exercise.…”
Section: The Effects Of Exercisementioning
confidence: 99%
“…Chronic exercise training has been shown to enhance myocardial diastolic function [55][56][57], alters calcium uptake in the SR [57], and induces sinus bradycardia [53]. Interestingly, exercise conditioning may potentially reverse diastolic dysfunction-associated pathologic hypertrophy [58] and/or with minimal effects on ischemia/reperfusion injury [59] while also lessening ageassociated declines in diastolic function [54].…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…Chronic exercise training causes a bene�cial adaptive response of the cardiovascular system, that is, decreased resting and submaximal heart rates and increased LV �lling time, venous return, and stroke volume [53,54]. Chronic exercise training has been shown to enhance myocardial diastolic function [55][56][57], alters calcium uptake in the SR [57], and induces sinus bradycardia [53].…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…position [2][3][4][5][6][7][8] . In general, the AT and peak VO2, which are determined from cardiopulmonary exercise testing, were lower in the supine position than in the upright position 5)8) .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported comparisons of cardiopulmonary responses during upright and recumbent (supine) exercises [2][3][4][5][6][7][8] . Generally, it has been reported that work performance in incremental exercise is enhanced in the upright position as .…”
mentioning
confidence: 99%